Diversification and overviews of anaerobic digestion of Cuban pig breeding - Sosa, R.; D?az, Y. M.; Cruz, Tamara; de la Fuente, J. L. (Cuban Journal of Agricultural Science, 2014)
This study shows the most recent advances of the ?Centro de Promoci?n y Desarrollo de Biog?s? (CPDB) about the use, diversification and perspectives of anaerobic digestion of Cuban pigs. Some of the reached results are the generation of electricity using biogas, the development of biodigesters of fixed domes and the tubular ones, the drying bed/biodigester system, and the characterization of biogas, produced in Cuba, not only with water wastes but also with residues of high content of animal fat. It is also stated the usage of new construction materials for repairing the biodigesters, and the experiences of the recycling of water. This study is also about the perspectives of the use of biogas in breeding pigs in Cuba. It can be concluded that the usage of biogas for cooking and generating electricity shows the development and diversification of this resource in Cuban agriculture. The results allowed characterizing the biogas and its more important indicators in the Cuban conditions. Besides, several plant systems of biogas have been evaluated and developed for small and medium pig productions. It is recommended to continue the researches and technology transfers in biogas plants that allow to accelerate, in short time, the use of these plants for the productions of cooperatives, small farms and state farms. It is suggested to continue the development of researches and technology transfers in prototypes of equipment for the use of biogas (lamps, refrigerators, electricity generators, among others). It is necessary to increase the training and organization as a way of increasing the number of specialists and technicians for working in plants and equipment design for the use of biogas, with the objective of carrying out constructions and installations in a short period. Key words: biogas, pig breeding, environment, generation of electricity